Revista Senhor: a influência da ilustração na formação do design editorial no Brasil - Oliveira Júnior, Adilson Gonzales de; Nakata, Milton Koji [UNESP] (My University, 2014)
Senhor Magazine’s editorial project was used as basis for several scientific studies as its content represents a turning point to national culture and it marks the decade of 1960 as one of the most significant projects of graphic design in Brazil. The present paper aims to analyze the illustration’s significance to the development of Brazilian’s editorial design and its object of study is Senhor Magazine due to the relevant connection between design and illustration. Therefore, a literature research addressing the history of editorial design in Brazil, as well as the influence of illustration in these projects was conducted. It was concluded that illustration was crucial for editorial design evolution in Brazil, and this relationship has been established since the early twentieth century. Therefore, only in the sixties it was accepted, and Senhor Magazine has become the biggest representation of this period.

O projeto editorial da Revista Senhor foi utilizado como base de estudo para inúmeros trabalhos científicos, pois seu conteúdo representa um momento de mudança na cultura nacional e marca a década de 60 como um dos projetos mais significativos da história do design gráfico no Brasil. O presente trabalho tem como objetivo analisar a influência da ilustração na formação do design editorial brasileiro e o objeto de análise é a Revista Senhor devido à relação significativa entre o design e a ilustração. Para isso foi realizada uma pesquisa bibliográfica que abordou a história do design editorial no Brasil, bem como a presença da ilustração nesses projetos. Conclui-se que a ilustração foi fundamental para formação do design editorial no Brasil e que essa relação foi estabelecida desde o início do século XX, mas somente na década de 60 teve seu reconhecimento, sendo que a Revista Senhor se tornou a maior representação desse momento.
Keywords: Illustration; Design; Graphic design; Editorial design; Ilustração; Design; Design gráfico; Design editorial